(untitled) (Economics and region, 2023)
The article substantiates the choice of a model of corporate social responsibility based on the method of analysis of hierarchies. Corporate social responsibility as a general scientific concept, when companies voluntarily decide to accept social, economic and environmental responsibilities for the best society and the environment. The purpose of the article is the practical recommendations of implementation of the method of analysis of hierarchies in the system of decision -making of corporate social responsibility. Five criteria (spheres) of corporate social responsibility have been identified: economic, ethical, political, social, environmental. Three models of corporate social responsibility are considered: TBL model, social responsibility pyramid A. Carroll, model of stakeholders. The concept of triple criterion as a concept of business construction, according to which entrepreneurs and managers should take into account not only the financial indicators but also the social and environmental results of the company. A. Carroll Pyramid is used as a management tool that allows you to determine the level of corporate social responsibility in the company and the need to develop a model of stakeholders of corporate social responsibility that managers are responsible for corporate decisions because they influence different stakeholders. Each business solution is associated with some costs that fall on certain stakeholders. At the same time, other stakeholders benefit from decisions. The theory of stakeholders defines the main social indicators of stakeholders, but it was not mentioned in relation to social procedures. The model of stakeholders of corporate social responsibility argues that everyone has equal rights and the legal rights of stakeholders should restrict the actions of corporations. Interestingly, this model views shareholders not as owners, but as investors. Other business factors may include work, materials, social infrastructure or market. Therefore, companies should create value for customers, suppliers, employees, communities and financiers. As a conclusion, the most adequate model of CSR is a triple criterion model – the weight of the final priority 0.51.